Effects of kenaf/polyester blending ratios on physical and mechanical properties of yarns produced from ring spinning system - Mohd Rusli, Najwa Wajihah (2019)
Yarns with natural-synthetic hybrid fibers are becoming increasingly popular with the increase of environmental awareness. This is mainly because the hybridization of fiber may reduce the use of synthetic fibers in the making of yarns. Note that polyester, an excellent synthetic fiber, is difficult to be recycled and is non-biodegradable. On the other hand, kenaf fiber has been proven to be biodegradable and compatible with the environment. This study observed on properties of kenaf/polyester hybrid yarns with different composition of kenaf that was spun using ring spinning system. The development of sliver was prepared by using carding process, the sliver was then inserted into ring spinning machine to produce hybrid yarns. The physical and mechanical analysis such as surface morphology, diameter of sliver and yarn, waste percentage, size and tensile strength test were conducted on sliver and yarn. Apart from that, the Analysis of Variance (ANOVA) via Minitab software was employed for quantitative evidence, and the morphology analysis of different kenaf composition was observed through Scanning Electron Microscope (SEM). At the beginning of this study, the optimum characteristics of kenaf/polyester sliver subjected to the different composition of kenaf were determined. Following this, kenaf/polyester hybrid yarn of three different weight ratios were developed (50:50, 60:40 and 70:30). The findings showed that the physical and mechanical properties of sliver and yarn could be effectively controlled by varying kenaf composition. The composition of 50% kenaf exhibited an excellent stress-strain response, tensile strength, Young’s Modulus and elongation percentage. The adhesion effects of both kenaf and polyester fibers created an interlocking structure that limited the extension of the yarns. This produced fibers with a higher bending load capacity. It was also noted that the kenaf/polyester hybrid (50% kenaf and 50% polyester) had improved physical and mechanical properties. Nonetheless, the subsequent increment in kenaf composition did not improve the strength of the yarn.